Host-parasite relationship during Epistylis sp (Ciliophora: Epistylididae) infestation in farmed cichlid and pimelodid fish - Padua, Santiago Benites de; Martins, Mauricio Laterca; Ramos Valladao, Gustavo Moraes [UNESP]; Utz, Laura; Zara, Fernando Jose [UNESP]; Ishikawa, Marcia Mayumi; Andrade Belo, Marco Antonio de [UNESP] (Empresa Brasil Pesq Agropec, 2016)
The objective of this work was to describe the host-Epistylis sp. relationship during infestation on farmed fish. Five Nile tilapia (Oreochromis niloticus) and ten hybrid surubim catfish (Pseudoplatystoma reticulatum x P corruscans), all diseased, were used for in vivo morphological analysis of sessile peritrichs by contrast microscopy. Fragments of infected tissues were subjected to histological processing and scanning electron microscopy. Epistylis sp. caused hemorrhagic ulcer disease, and cichlids were more prone to develop infestations throughout the body surface due to the attachment of the colonies to the scales, which did not occur with pimelodids. Multifocal granulomatous dermatitis was observed, associated with the hydropic degeneration of the epithelium and to ulcerative areas of necrosis. Microscopic examination showed the presence of bacterial microflora associated to Epistylis sp. peduncles. Therefore, this species can be considered a portal of entry for opportunistic bacteria.
Keywords: Oreochromis niloticus; Pseudoplatystoma reticulatum; Pseudoplatystoma corruscans; histopathology; pathogenesis; sessile peritrich